Genome-wide identification of PEBP gene family in Hedychium coronarium - Wang, Qin; Zhou, Yiwei; Wang, Fang; Li, Xinyue; Yu, Yunyi; Yu, Rangcai; Fan, Yanping (Frontiers in Plant Science, 2025)
The Phosphatidylethanolamine-binding protein (PEBP) gene family plays a crucial role in plant growth and development, particularly in regulating flowering time and morphogenesis. However, the diversity, expression patterns, and functions of PEBP genes in Hedychium coronarium remain largely unexplored. In this study, 14 HcPEBP genes were identified and classified into MFT, FT, and TFL1 subfamilies based on phylogenetic analysis. Intraspecific collinearity analysis revealed three collinear relationships within the HcPEBP gene family. Interspecific collinearity analysis across H. coronarium, rice, wild banana, and pineapple highlighted the evolutionary significance of specific PEBP genes. Motifs DPDxP and GxHR are conserved in HcPEBPs, which are essential for anion-binding activity. At the same position in the C-terminus, FT-likes contain the xGxGGR motif, while TFL1-likes possesses the TAARRR motif. 64.3% of HcPEBP genes consist of four exons and three introns. Promoter regions of HcPEBP genes are enriched with light-responsive elements, suggesting a primary response to light signals. Expression patterns analysis by qRT-PCR showed that seven FT-like genes are predominantly expressed in leaves, with increased expression during the transition from vegetative to reproductive growth. HcPEBP11, a FT-like gene, is highly expressed in inflorescence buds. Overexpression of HcPEBP11 in tobacco induced early flowering, confirming its role in promoting flowering. This study provides a foundation for further research on the biological functions of the PEBP gene family in H. coronarium and elucidates the role of HcPEBP11 in flowering regulation.